A method for improving the stability of ligands on leaching resin

By using sodium alginate and cyclodextrin on the extracted resin to form a composite film, the problem of insufficient ligand stability is solved, and the service life of the resin and the reduction of production costs are achieved.

CN115710359BActive Publication Date: 2025-04-08CHINA INSTITUTE OF ATOMIC ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211453478.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-21
Publication Date
2025-04-08
Estimated Expiration
2042-11-21

AI Technical Summary

Technical Problem

The ligand stability of existing extracted resins is weak and easy to lose, resulting in a decrease in adsorption effect and a shortened resin service life.

Method used

The composite film was formed to stabilize the ligand by soaking the extract resin in a mixed aqueous solution of sodium alginate and cyclodextrin and adding a soluble divalent cationic salt solution.

Benefits of technology

It improves the stability of ligands on the extract resin, extends the service life of the resin, and reduces production costs, and is suitable for large-scale production and recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115710359B_ABST
    Figure CN115710359B_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the stability of ligands on leaching resin. The leaching resin is soaked in a mixed aqueous solution of sodium alginate and cyclodextrin, then a soluble divalent cation salt solution is added to carry out a surface gelation reaction, and the leaching resin with good ligand stability is obtained by suction filtration, washing and drying. The method is simple, low in raw material cost, good in stability and performance, and easy to produce and use on a large scale. Compared with untreated leaching resin, the recycling rate is high, the effect is good, and the service life of the resin is effectively improved. The sodium alginate and cyclodextrin used in the invention have strong hydrophilicity, and the method can be widely used to improve the stability of ligands on leaching resins used in water phases or polar solvents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of extraction and separation, and particularly relates to a method for improving the stability of ligands on leaching resin. Background Art

[0002] Extraction resin refers to a solid phase adsorption / extraction material formed by loading organic ligand molecules with specific coordination functions onto a carrier. It is widely used in the separation and extraction of various metal ions in hydrometallurgy and nuclear industry, as well as the treatment of metal-containing wastewater.

[0003] The preparation of leaching resin can be divided into the covalent reaction of organic ligands and carriers and the non-covalent method of loading ligands onto carriers. In the covalent method, the ligands and carriers are connected by covalent bonds. During use, the ligands and carriers are firmly bound and not easy to lose; but covalent chemical reactions are complex, the preparation process is difficult, the cost is high, and it is difficult to produce and use on a large scale; non-covalent methods are achieved by intermolecular interactions between ligands and carriers, which are simple to operate, low in cost, and easy to industrialize, but the binding force between the ligands and carriers is weak, and the ligands are easily lost during use, which not only leads to a decrease in adsorption effect, but also reduces the resin cycle performance, shortens the resin service life, and increases production costs. Summary of the invention

[0004] In view of the above-mentioned technical problems existing in the prior art, the object of the present invention is to provide a method for stabilizing the ligand by in-situ coating of a sodium alginate and cyclodextrin composite film, thereby improving the stability of the ligand on the leaching resin and prolonging the service life and cycle number of the resin, which is simple to operate, low-cost, and easy to mass produce.

[0005] To achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows: A method for improving the stability of the ligand on the leaching resin comprises the following steps:

[0006] (1) soaking the leaching resin in a mixed aqueous solution of sodium alginate and cyclodextrin and stirring;

[0007] (2) adding the soaked leaching resin into a soluble divalent cation salt solution in portions and rapidly stirring to obtain a leaching resin after a surface gelation reaction;

[0008] (3) The surface-gelled leaching resin is filtered and dried to obtain a leaching resin with good ligand stability.

[0009] Furthermore, in the step (1), the temperature of the mixed aqueous solution of sodium alginate and cyclodextrin is 20-45° C., and the soaking time is 0.1-2 hours; after the soaking is completed, the liquid is drained under negative pressure to obtain the soaked leaching resin.

[0010] Furthermore, in the step (1), the total concentration of the mixed aqueous solution of sodium alginate and cyclodextrin is 0.1-3wt%, and the mass ratio of cyclodextrin to sodium alginate is 1:1-20.

[0011] Furthermore, in the step (1), the cyclodextrin is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

[0012] Furthermore, in the step (2), the soaked leaching resin is added into a soluble divalent cation salt solution with a mass concentration of 1-10 wt% in 5-10 times.

[0013] Furthermore, in step (2), the soluble divalent cation salt solution is one or more of nitrates and hydrochlorides of magnesium, calcium, strontium, and barium.

[0014] Furthermore, in the step (3), the surface gelled leaching resin is vacuum filtered, washed with deionized water and dried to obtain a leaching resin with good ligand stability.

[0015] Furthermore, in the step (3), the surface gelled leaching resin is vacuum filtered, washed with deionized water for 2 to 4 times, and vacuum dried at 60 to 120° C. for 2 to 8 hours to obtain a leaching resin with good ligand stability.

[0016] Furthermore, the leaching resin is one of SR resin, ZR resin, TEVA resin, UTEVA resin, DGA resin, TBP resin, Cs resin, TRU resin, and TK200 / 400 resin.

[0017] The beneficial effects brought by the technical solution of the present invention are as follows: a method for improving the stability of the ligand on the leaching resin, wherein the leaching resin is immersed in a mixed aqueous solution of sodium alginate and cyclodextrin, then a soluble divalent cation salt solution is added to carry out a surface gelation reaction, and the leaching resin with good ligand stability is obtained by suction filtration, washing and drying; the method of the present invention is simple, has low raw material cost, good stability, good performance, is easy to produce and use on a large scale, has good recycling effect, and effectively improves the service life of the resin; and the sodium alginate and cyclodextrin used in the present invention have strong hydrophilicity, and the method of the present invention can be widely used to improve the stability of the ligand on the leaching resin used in an aqueous phase or a polar solvent. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a scanning electron microscope image of the SR resin treated by the method of Example 2 of the present invention;

[0019] Figure 2 is a comparison diagram of the adsorption-regeneration cycle effect of the leaching resin treated by the method of Example 2 of the present invention and the untreated leaching resin;

[0020] Figure 3 is a comparison diagram of the adsorption-regeneration cycle effect of the leaching resin treated by the method of Example 3 of the present invention and the untreated leaching resin;

[0021] Figure 4 is a comparison diagram of the adsorption-regeneration cycle effect of the leaching resin treated by the method of Example 4 of the present invention and the untreated leaching resin;

[0022] Figure 5 is a comparison diagram of the adsorption-regeneration cycle effect of the leaching resin treated by the method of Example 5 of the present invention and the untreated leaching resin;

[0023] Figure 6 It is a comparison diagram of the adsorption-regeneration cycle effect of the leaching resin treated by the method of Example 6 of the present invention and the untreated leaching resin. DETAILED DESCRIPTION

[0024] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0025] Embodiment 1

[0026] The embodiment of the present invention provides a method for improving the stability of ligands on leaching resin, comprising the following steps:

[0027] (1) soaking the leaching resin in a mixed aqueous solution of sodium alginate and cyclodextrin and stirring;

[0028] (2) adding the soaked leaching resin into a soluble divalent cation salt solution in portions and rapidly stirring to obtain a leaching resin after a surface gelation reaction;

[0029] (3) The surface gelled leaching resin is filtered and dried to obtain a leaching resin with good ligand stability. Sodium alginate undergoes a cross-linking reaction with divalent cations on the surface of the leaching resin to form a protective film; the hydrophobic cavity of cyclodextrin can form an inclusion complex with the hydrophobic part of the ligand, which plays a role in stabilizing the ligand; the polar functional groups such as carboxyl and hydroxyl groups on sodium alginate and cyclodextrin can form intermolecular interactions such as hydrogen bonds, electrostatics and strong dipole interactions with the polar part of the ligand, which can further stabilize the ligand and make it less likely to be lost during use, effectively improving the stability of the ligand in the resin and extending the service life of the resin.

[0030] Preferably, in step (1), the temperature of the mixed aqueous solution of sodium alginate and cyclodextrin is 20-45° C., and the soaking time is 0.1-2 h; after the soaking, the liquid is drained under negative pressure to obtain the soaked leaching resin.

[0031] Preferably, in step (1), the total concentration of the mixed aqueous solution of sodium alginate and cyclodextrin is 0.1-3 wt %, and the mass ratio of cyclodextrin to sodium alginate is 1:1-20.

[0032] Preferably, in step (1), the cyclodextrin is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

[0033] Preferably, in step (2), the soaked leaching resin is added into a soluble divalent cation salt solution having a mass concentration of 1-10 wt% in 5-10 times.

[0034] Preferably, in step (2), the soluble divalent cation salt solution is one or more of the nitrates and hydrochlorides of magnesium, calcium, strontium and barium.

[0035] Preferably, in the step (3), the surface gelled leaching resin is vacuum filtered, washed with deionized water and dried to obtain a leaching resin with good ligand stability.

[0036] Preferably, in the step (3), the surface gelled leaching resin is vacuum filtered, washed with deionized water for 2 to 4 times, and vacuum dried at 60 to 120° C. for 2 to 8 hours to obtain a leaching resin with good ligand stability.

[0037] Preferably, the leaching resin is one of SR resin, ZR resin, TEVA resin, UTEVA resin, DGA resin, TBP resin, Cs resin, TRU resin, and TK200 / 400 resin. The sodium alginate and cyclodextrin both have strong hydrophilicity. The method of the embodiment of the present invention is suitable for improving the stability of the ligand on the leaching resin used in the aqueous phase or polar solvent, and is not limited to the above resins.

[0038] Embodiment 2

[0039] The method of Example 1 of the present invention is used to improve the stability of the ligand on the leaching resin.

[0040] Accurately weigh 1g of sodium alginate (50mPa.s, 1%, 20℃) and 0.25g of β-cyclodextrin, add them to 100mL of water, stir them with a constant temperature magnetic force at 40℃, and after they are completely dissolved, add 10g of commercial SR resin (particle size 50-100μm, produced by TriskemInternational, France), and continue stirring for 1.5h; then, vacuum filter in a sand core funnel until no leakage is extracted, then add the soaked SR resin into 50mL of 4wt% calcium nitrate solution, stir rapidly, stop stirring and filter after 120min, and wash three times with 20ml of deionized water; finally, transfer the solid to a vacuum oven and vacuum dry it at 60℃ for 8 hours to obtain 9.7g of the final product.

[0041] See attached Figure 1 , indicating that the SR resin stabilized by the composite membrane of sodium alginate and cyclodextrin used in the embodiment of the present invention still has good dispersibility after surface modification.

[0042] 200 mg of the product obtained in the embodiment of the present invention was added to 20 mL of 100 mg / L strontium nitrate solution, stirred at 25° C., centrifuged after 6 h, and then the strontium ion concentration was analyzed by ICP-AES, and the adsorption amount of strontium ions was calculated using formula (1).

[0043] The leaching resin of the present invention after adsorbing strontium ions was soaked in 50 mL of deionized water and stirred. After 2 hours, the resin was centrifuged and the upper liquid was removed. This operation was repeated 4 times and the clean solid was dried to obtain the regenerated resin. The regenerated resin was then operated for 6 cycles according to the above adsorption-regeneration method; at the same time, the commercial SR resin was also subjected to 6 adsorption-regeneration cycles for comparison.

[0044] The calculation method of the adsorption amount Q of strontium ions is as follows:

[0045]

[0046] Where C0 is the initial concentration of strontium ions, C e is the adsorption equilibrium concentration of strontium ions, in mg / L; m is the mass of the adsorbent material, in g; V is the volume of the radioactive liquid, in L.

[0047] See attached Figure 2 , indicating that the leaching resin of the embodiment method of the present invention has good cycle performance and effectively improves the service life of the leaching resin.

[0048] Embodiment 3

[0049] The method of Example 1 of the present invention is used to improve the stability of the ligand on the leaching resin.

[0050] Accurately weigh 0.5g sodium alginate (1000mPa.s, 1%, 20℃) and 0.5g β-cyclodextrin, add to 100mL water, stir with constant temperature magnetic force at 25℃, wait for them to be completely dissolved, add 5g commercial DGA resin (particle size 100-150μm, produced by Triskem International, France), continue stirring for 0.5h; then, vacuum filter in a sand core funnel until no leakage is extracted, add the soaked DGA resin to 50mL 3wt% calcium nitrate solution, stir rapidly, stop stirring and filter after 60min, wash three times with 20ml deionized water; finally, transfer the solid to a vacuum oven, vacuum dry at 90℃ for 3 hours, and obtain 4.9g final product. The rest is the same as in Example 1.

[0051] The product of the embodiment of the present invention is used to adsorb strontium ions, and the rest is the same as that of the second embodiment.

[0052] Embodiment 4

[0053] Accurately weigh 1g of sodium alginate (200mPa.s, 1%, 20°C) and 1g of α-cyclodextrin, add them to 100mL of water, stir them with constant temperature magnetic force at 30°C, wait for them to be completely dissolved, add 20g of TBP resin (self-made, TBP is loaded on P120 resin carrier by vacuum infusion method), continue stirring for 20min; then, vacuum filter in a sand core funnel until no leakage is extracted, add the soaked SR resin to 50mL of 4wt% calcium nitrate solution, stir rapidly, stop stirring and filter after 300min, wash three times with 20ml of deionized water; finally, transfer the solid to a vacuum oven, vacuum dry it at 120°C for 2 hours, and obtain 10.1g of the final product. The rest is the same as in Example 1.

[0054] The product of the embodiment of the present invention is used to adsorb strontium ions, and the rest is the same as that of the second embodiment.

[0055] Embodiment 5

[0056] Accurately weigh 1g of sodium alginate (50mPa.s, 1%, 20°C) and 1g of β-cyclodextrin, add them to 100mL of water, stir them with constant temperature magnetic force at 40°C, and after they are completely dissolved, add 10g of commercial ZR resin (particle size 100-150μm, produced by TriskemInternational, France), and continue stirring for 1h; then, vacuum filter in a sand core funnel until no leakage is extracted, add the soaked ZR resin to 50mL of 5wt% calcium nitrate solution, stir rapidly, stop stirring and filter after 240min, and wash three times with 20ml of deionized water; finally, transfer the solid to a vacuum oven, vacuum dry it at 80°C for 6 hours, and obtain 9.7g of the final product. The rest is the same as in Example 1.

[0057] The product of the embodiment of the present invention is used to adsorb zirconium ions, and the rest is the same as that of the second embodiment.

[0058] Embodiment 6

[0059] Accurately weigh 3g of sodium alginate (50mPa.s, 1%, 20℃) and 0.25g of β-cyclodextrin, add them into 100mL of water, stir them with magnetic force at constant temperature at 30℃, and after they are completely dissolved, add 30g of homemade SR resin (homemade, 4,4'-di(tetra-tert-butylcyclohexyl)-18-crown-6) loaded on P120 resin carrier by vacuum infusion method), and continue stirring for 2h; then, vacuum filter in a sand core funnel until no leakage is extracted, then add the soaked homemade SR resin into 100mL of 3wt% calcium nitrate solution, stir rapidly, stop stirring and filter after 100min, and wash three times with 50ml of deionized water; finally, transfer the solid to a vacuum oven and vacuum dry it at 80℃ for 6 hours to obtain 31.3g of the final product.

[0060] The product of the embodiment of the present invention is used to adsorb strontium ions, and the rest is the same as that of the second embodiment.

[0061] See attached Figure 3 , 4 , 5, 6. The performance of the resin treated by the method of the embodiment of the present invention based on the commercial or homemade resin changes little after multiple cycles, indicating that the resin treated by the method of the embodiment of the present invention has good stability, can be recycled multiple times, has good performance, and effectively extends the service life of the resin.

[0062] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for improving the stability of ligands on leaching resins, characterized in that: The following steps are involved: (1) soaking the leaching resin in a mixed aqueous solution of sodium alginate and cyclodextrin, and stirring; the total concentration of the mixed aqueous solution of sodium alginate and cyclodextrin is 0.1-3wt%, and the mass ratio of cyclodextrin to sodium alginate is 1:1-20; (2) adding the soaked leaching resin into a soluble divalent cation salt solution in portions and rapidly stirring to obtain a leaching resin after a surface gelation reaction; (3) The surface-gelled leaching resin is filtered and dried to obtain a leaching resin with good ligand stability.

2. A method for improving the stability of ligands on leaching resin according to claim 1, characterized in that: In the step (1), the temperature of the mixed aqueous solution of sodium alginate and cyclodextrin is 20-45° C., and the soaking time is 0.1-2 hours; after the soaking is completed, the liquid is drained under negative pressure to obtain the soaked leaching resin.

3. The method for improving the stability of ligands on leaching resin according to claim 1, characterized in that: In the step (1), the cyclodextrin is one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

4. The method for improving the stability of ligands on leaching resin according to claim 1, characterized in that: In the step (2), the soaked leaching resin is added into a soluble divalent cation salt solution with a mass concentration of 1-10 wt% in 5-10 times.

5. The method for improving the stability of ligands on leaching resin according to claim 1, characterized in that: In the step (2), the soluble divalent cation salt solution is one or more of the nitrates and hydrochlorides of magnesium, calcium, strontium, and barium.

6. The method for improving the stability of ligands on leaching resin according to claim 1, characterized in that: In the step (3), the surface gelled leaching resin is vacuum filtered, washed with deionized water and dried to obtain a leaching resin with good ligand stability.

7. The method for improving the stability of ligands on leaching resin according to claim 1, characterized in that: In the step (3), the surface gelled leaching resin is vacuum filtered, washed with deionized water for 2 to 4 times, and vacuum dried at 60 to 120° C. for 2 to 8 hours to obtain a leaching resin with good ligand stability.

8. The method for improving the stability of ligands on leaching resin according to claim 1, characterized in that: The leaching resin is one of SR resin, ZR resin, TEVA resin, UTEVA resin, DGA resin, TBP resin, Cs resin, TRU resin, and TK200 / 400 resin.

Citation Information

Patent Citations

  • Preparation method and application of novel adsorbent resin

    CN102091603A

  • Carrier modified extraction-elution resin for dyeing wastewater decoloration and preparation method thereof

    CN107325216A